2022
DOI: 10.1371/journal.pone.0273963
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ perceptions and experiences of e-internships during the COVID-19 pandemic: A phenomenological study

Abstract: Background Clinical internship is an indispensable stage for nursing students to graduate successfully and become qualified nurses. However, COVID-19, a novel coronavirus disease with strong human-to-human transmission, hit China in late 2019 and forced the Chinese government to suspend classes and clinical internships. To cope with this situation, e-internship, which facilitate varied interactions without the need for direct contact, is used as an alternative strategy to help nursing students continue their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The positive learning experience could be related to the self-confidence of being able to practice procedures in a less intimidating environment. Similar sentiments were shared by Badowski et al (2021); Fung et al (2021); Yi et al (2022) and Saab et al (2022). In this regard, students had various opportunities to carry out trial and error in the reprioritization of nursing diagnosis while receiving prompt feedback, thus creating positive learning experiences (Badowski et al, 2021;Saab et al, 2022).…”
Section: Benefits Of the Use Of Digital Technology In Clinical Learningmentioning
confidence: 78%
See 4 more Smart Citations
“…The positive learning experience could be related to the self-confidence of being able to practice procedures in a less intimidating environment. Similar sentiments were shared by Badowski et al (2021); Fung et al (2021); Yi et al (2022) and Saab et al (2022). In this regard, students had various opportunities to carry out trial and error in the reprioritization of nursing diagnosis while receiving prompt feedback, thus creating positive learning experiences (Badowski et al, 2021;Saab et al, 2022).…”
Section: Benefits Of the Use Of Digital Technology In Clinical Learningmentioning
confidence: 78%
“…This study also revealed several challenges about digital technology utilization for clinical learning (Badowski et al, 2021;Bryan et al, 2022;Flo et al, 2021;Fung et al, 2021;Hu et al, 2022;Jiménez-Rodríguez & Arrogante, 2020;Kim et al, 2021;Mbombi et al, 2022;Ndayisenga et al, 2022;Oducado & Soriano, 2021;Saab et al, 2022;Yi et al, 2022). Technical challenges such as accessibility or usability issues and unavoidable technical difficulties were cited as impediments to the use of digital technology among undergraduate nursing students during the COVID -19 pandemic.…”
Section: Challenges Of Digital Technologymentioning
confidence: 81%
See 3 more Smart Citations